2003
DOI: 10.1139/x03-007
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol in ponderosa pine as an indicator of physiological injury from fire and its relationship to secondary beetles

Abstract: Sixteen days after a September wildfire, ethanol and water were measured in phloem and sapwood at breast height and the base of Pinus ponderosa Dougl. ex P. & C. Laws. with zero (control), moderate, heavy, and severe crown scorch. The quantity of ethanol increased with each level of injury, resulting in trees with severe scorch containing 15 and 53 times more phloem and sapwood ethanol, respectively, than controls. Ethanol concentrations in the sapwood and adjacent phloem were related, probably as a result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 42 publications
2
49
0
Order By: Relevance
“…While neither beetle is considered a primary bark beetle capable of attacking and killing healthy trees, their signs may be good external indicators that a conifer sustained substantial injuries from fire. Kelsey and Joseph (2003) reported increased ethanol production in fire-injured trees, which was associated with increased red turpentine beetle landing rates compared to control trees. Short-term decreases in resin flow immediately after fire was cited as the possible mechanism leading to increased attacks by Ips beetles in fire-injured red pine (Pinus resinosa Aiton) (Lombardero et al, 2006).…”
Section: Modelmentioning
confidence: 96%
“…While neither beetle is considered a primary bark beetle capable of attacking and killing healthy trees, their signs may be good external indicators that a conifer sustained substantial injuries from fire. Kelsey and Joseph (2003) reported increased ethanol production in fire-injured trees, which was associated with increased red turpentine beetle landing rates compared to control trees. Short-term decreases in resin flow immediately after fire was cited as the possible mechanism leading to increased attacks by Ips beetles in fire-injured red pine (Pinus resinosa Aiton) (Lombardero et al, 2006).…”
Section: Modelmentioning
confidence: 96%
“…They are consistent with the view of Lindgren and Raffa (2013) who assert treekilling has evolved from saprophagy in response to inter-specific competition since the weakened resources are effectively undefended and potentially available by a number of other species. The pressure exerted by competing secondary species may even be enhanced by primary attractants such as ethanol produced by dead, fermenting resources (Klimetzek et al, 1986;Joseph et al, 2001;Kelsey and Joseph, 2003). Wind-felled trees, however, constitute useful hosts for aggressive beetles at endemic population levels because of their low defense levels and, at the same time, offer a substantial nutritional resource to the insects, facilitating successful reproduction, growth and development (Louis et al, 2014).…”
Section: Mej Reactionmentioning
confidence: 99%
“…Saint-Germain et al (2007) showed that secondary bark beetles use primary attractants to locate suitable patches, but then land at random on individual trees. Ethanol, produced by fire-or water-stressed trees have been shown to elicit positive response from bark beetles (Joseph et al, 2001;Kelsey and Joseph, 2003), although Klimetzek et al (1986) contend that the most aggressive beetles tend to avoid ethanol as it may indicate high inter-specific competition. Finally, visual cues may play a role in the selection process: some ''visual specialists" show strong preferences toward the silhouette of their host (standing vs. fallen tree) and most beetles show some capacity to visually discriminate traps of different shape and color (Byers, 1993;Strom et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, species richness and diversity were greater in burned areas than in salvaged areas, which suggests that greater numbers of beetle species were attracted to the recently burned, larger-sized pieces of CWD (Gilmore et al 2003), and to fire-damaged and dead residual trees. There is evidence that fire-damaged trees produce greater amounts of ethanol and, therefore, attract greater numbers of subcortical beetles than do undamaged trees (Santoro et al 2000;Kelsey and Joseph 2003). Although burning eventually results in lowered population levels of early-successional subcortical beetles, it may actually result in a greater species richness and diversity on the sub-boreal landscape (Santoro et al 2000).…”
Section: Subcortical Insect Trap Catchesmentioning
confidence: 99%